Production of Cloned Pigs Derived from Double Gene Knockout Cells Using CRISPR/Cas9 System and MACS-based Enrichment System - Bumrae Cho; Su Jin Kim; Eun-Jin Lee; Sun Mi Ahn; Jin Seok Lee; Dal-young Ji; Sang Hoon Lee; Jung-Taek Kang (The Korean Society of Animal Reproduction and Biotechnology, 2018)
Pigs are considered as optimal donor animal for the successful xenotransplantation. To increase the possibility of clinical application, genetic modification to increase compatibility with human is an important and essential process. Genetic modification technique has been developed and improved to produce genetically modified pigs rapidly. CRISPR/Cas9 system is widely used in various fields including the production of transgenic animals and also can be enable multiple gene modifications. In this study, we developed new gene targeting vector and enrichment system for the rapid and efficient selection of genetically modified cells. We conducted co-transfection with two targeting vectors for simultaneous inactivation of two genes and enrichment of the genetically modified cells using MACS. After this efficient enrichment, genotypic analysis of each colony showed that colonies which have genetic modifications on both genes were confirmed with high efficiency. Somatic cell nuclear transfer was conducted with established donor cells and genetically modified pigs were successfully produced. Genotypic and phenotypic analysis of generated pigs showed identical genotypes with donor cells and no surface expression of α-Gal and HD antigens. Furthermore, functional analysis using pooled human serum revealed dramatically reduction of human natural antibody (IgG and IgM) binding level and natural antibody-mediated cytotoxicity. In conclusion, the constructed vector and enrichment system using MACS used in this study is efficient and useful to generate genetically modified donor cells with multiple genetic alterations and lead to an efficient production of genetically modified pigs.